IMPACT OF PHYSICO-CHEMICAL PROPERTIES OF CASING SOIL ON SPOROPHORE DEVELOPMENT AND YIELD OF WHITE SUMMER MUSHROOM, CALOCYBE INDICA P&C - VANDANA PANDEY; K. K. MISHRA (The Bioscan, 2014)
Experiment was conducted to find out the effect of casing soil and their physico-chemical properties on pinhead initiation and productivity of Calocybe indica. Six casing soils viz Farm Yard Manure (FYM), Spent Compost (SC),Sandy Soil (SS), FYM +SC (1:2), FYM +SC (2:1)and FYM +SS+SC (2:1:1) were taken and each was sterilized with 4 per cent formalin solution. The casing soil prepared using FYM +SC+SS (2:1:1) took minimum average days (8) for pinhead initiation. The significantly higher yield (529.00 g/kg dry substrate) was obtained with FYM+SC (1:2). Sandy soil having slightly alkaline pH (7.05), low nitrogen content (2.68%), low phosphorus content (0.49%) and potassium content (0.44) had lowest yield (226.33 g/kg dry substrate) with minimum number of fruiting bodies (17).